Study on anxiety and depression of men who have sex with men: An application of group-based trajectory model - Wu, Dan; Zhong, Xiaoni; Deng, Ruibin; Pan, Hong; Gao, Yuwen; Lin, Bing; Tang, Xian; Dai, Jianghong; Liang, Hao; Huang, Ailong (Frontiers in Psychology, 2023)
The prevalence of anxiety and depression is high among men who have sex with men (MSM), but limited studies focus on their development trends. This study examined the prevalence and influencing factors of anxiety and depression in HIV-negative MSM. In this study, 711 subjects were followed up every 24 weeks for 96 weeks. A group-based trajectory model was used to identify different development trends and a logistic regression model was used to explore the influencing factors of different trajectories. Low, moderate, and high anxiety groups accounted for 32.56, 56.12, and 11.32%; and low and high depression groups accounted for 73.90 and 26.10%. High anxiety was associated with a lower education degree, little HIV-related knowledge, and other characteristics (more agreed that “HIV is a threat to me/my family,” had high frequency of seeking sexual partners via the Internet, had a history of sexually transmitted disease (STD), and a sense of discrimination by doctors). High depression was associated with a lower education degree, little HIV-related knowledge, being bisexual and the following characteristics: they felt that HIV infection rate of MSM around them was high, and more agreed that “HIV is a threat to me/my family,” had a high frequency of seeking sexual partners through the Internet and alcohol drinking, had a history of STD, and felt being discriminated against by doctors and others. There is heterogeneity in the development trends of anxiety and depression. We need to improve intervention in the mental health of MSM, especially those with high anxiety and depression development trends. Clinical Trial Registration [http://www.chictr.org.cn/showproj.aspx?proj=5716], identifier [ChiCTR-TRC-13003849].